Evaluation of Malatya Grand Mosque Ornaments Using the Morphological Analysis Method - Sahin, Murat; Olgun, Tuba Nur; Akbulut, Pinar (Istanbul Univ, Research Inst Turkology, Dept Art History, 2025)
The Malatya Ulu Mosque is one of the unique works of the Seljuk State in Anatolia in terms of its applied plan scheme, technical features, materials and ornaments. The decoration, ornamentation elements and glazed brick technique used in the mosque were influential in the development of Turkish-Islamic decorative art in Anatolia. The aim of this study is to analyze the ornaments of the Malatya Ulu Mosque, one of the architectural works of the Seljuk Period, and in this context, to draw attention to the importance of preserving cultural heritage through decorative elements. Considering the value of the building decorations of the period in terms of Turkish-Islamic architecture, it is understood that buildings with similar characteristics, especially the Malatya Ulu Mosque, need to be evaluated in depth in terms of their decorative features when they are taken under protection. In the study, the forms found in the ornaments on the east and west portals, the mihrab, and the courtyard of the Malatya Ulu Mosque were classified under four separate headings. According to this classification, each ornaments was examined morphologically at microscale usingfractal analysis method. Accordingly, the results obtained show that the fractal values of the muqarnas on the crown gates are higher than those of the other decorative elements. These are followed by geometric interlaces and motifs, and vegetal motifs and moldings respectively. The fractal values of these three elements are quite close to each other. These data show that the muqarnas on the crown gate have a more complex geometry than the other decorative elements.
Malatya Ulu Camii Bezemelerinin Morfolojik Analiz Yöntemiyle Değerlendirilmesi
Keywords: Malatya Grand Mosque; Morphological Analysis; Ornament; Fractal Analysis; Geometric Form